Too tired to engage? the impact of emotional exhaustion on outsourced employees with job satisfaction as a mediating variable - Sri Hidayah, Rahma Dini; Erlin, Nia Ariyani (Institute of Computer Science (IOCS), 2025)
Employee engagement is essential to enhancing organizational performance; however, it may be adversely affected by emotional exhaustion, particularly among outsourced workers who often face unique challenges in the workplace. Although employee engagement plays a critical role, there has been insufficient focus on how emotional exhaustion diminishes engagement, particularly among outsourced industrial workers who often encounter intense job demands and limited support. This research seeks to investigate the influence of emotional exhaustion on employee engagement, with job satisfaction considered as a mediating factor. This research explores how emotional exhaustion impacts employee engagement, with job satisfaction functioning as an intermediary in the relationship. The focus is on outsourced personnel working in the Inventory Unit at PT Semen Padang. Utilizing a quantitative method and survey data from 52 outsourced workers, This research utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships between variables The analysis indicates that emotional exhaustion does not directly influence engagement. Instead, it significantly lowers job satisfaction, which subsequently enhances engagement demonstrating a full mediation effect. align with the Job Demands–Resources (JD-R) model, emphasizing the buffering function of job satisfaction against the negative impact of emotional stress. Practical implications include the need for management to enhance psychological support, stress management, and communication to improve employee satisfaction and engagement. Future research is recommended to explore additional variables and diverse employee populations to deepen the understanding of factors influencing engagement